The Predictive Value of Tagalog Voice Morphology in Filler-Gap Dependency Formation - Pizarro-Guevara, Jed Sam; Wagers, Matthew (Frontiers in Psychology, 2020)
Research has shown that when processing filler-gap dependencies (FGDs), comprehenders do not wait until they encounter all of the bottom-up information in the input. Instead, they use various types of linguistic information to predictively posit a gap that would allow the FGD to be resolved. They can use syntactic, lexical, morphological, and prosodic. Here we examine whether Tagalog comprehenders use the language's voice morphology to guide their incremental interpretations. Comprehenders used voice to actively associate the filler with the gap (experiment 1). The way in which they used voice varied by type and varied across FGDs (experiment 2). In an acceptability judgment study (experiment 3), agent voice had high cue validity across the board, while patient voice had variable, FGD-specific cue validity. We argue that comprehenders used FGD-specific cue validities when processing FGDs, but they also engaged with other classes of linguistic information, including (but not limited to) information about the structural similarities and the thematic complexity of the FGDs involved, and the relative frequency of voice in the language.